Synthesis of Microcrystals of the [Fe(L)(bipy)] Spin Crossover Coordination Polymer in a Poly‐4‐vinylpyridine Matrix. Issue 8 (17th June 2014) - Göbel, Christoph; Palamarciuc, Tatiana; Lochenie, Charles; Weber, Birgit
Abstract Microcrystals of the spin‐crossover coordination polymer [FeL(bipy)] (L=[3, 3′]‐[1, 2‐phenylenebis(iminoethylidyne)]bis‐(2, 4‐pentanedionato)(2‐), bipy=4, 4′‐bipyridine) have been prepared in a poly(4‐vinylpyridine) (P4VP) matrix. This was done by sequential addition of the iron(II) precursor complex and the bridging ligand bipy to a P4VP matrix, and by repetition of this cycle. The obtained composite material was characterized using TEM, SEM, XRPD, and SQUID measurements, and Mössbauer spectroscopy. With repeating cycles, the size of the [FeL(bipy)] crystals in the P4VP matrix increases from submicrometer to micrometer dimensions. A strong dependence on the number of cycles is observed. Above a critical size and concentration, the microcrystals show the same cooperative spin transition as the bulk material. No indication for a gradual spin transition is observed, but the remaining iron centers are either high‐spin or low‐spin depending on the coordination environment.